2021
DOI: 10.3390/en14206661
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Performances of a Diesel Engine Operating on Blended and Emulsified Biofuels from Rapeseed Oil

Abstract: The article discusses the possibility of using blended biofuels from rapeseed oil (RO) as fuel for a diesel engine. RO blended diesel fuel (DF) and emulsified multicomponent biofuels have been investigated. Fuel physicochemical properties have been analyzed. Experimental tests of a diesel engine D-245 in the operating conditions of the external characteristic curve and the 13-mode test cycle have been conducted to investigate the effect of these fuels on engine performances. CFD simulations of the nozzle inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Non-condensable gas soluted in liquid fuel has an impact on nozzle internal flow mainly during needle valve opening and closing (especially for pilot injection) and/or under super high injection pressure (hydraulic flip conditions). Our previous studies performed for the serial AZPI nozzle [61][62][63] showed that super-cavitation and hydraulic flips do not occur under pressure conditions corresponding to the real operating conditions of the diesel engine D243 that equips AZPI nozzles. For the investigated injection regime (corresponding to the rated operating conditions of the D243 diesel engine, see Figure 18), the main portion of the fuel (74% of cycle delivery) is injected into the cylinder when the nozzle needle is at the maximum lift.…”
Section: Flow Passage Geometry Of Nozzlesmentioning
confidence: 99%
“…Non-condensable gas soluted in liquid fuel has an impact on nozzle internal flow mainly during needle valve opening and closing (especially for pilot injection) and/or under super high injection pressure (hydraulic flip conditions). Our previous studies performed for the serial AZPI nozzle [61][62][63] showed that super-cavitation and hydraulic flips do not occur under pressure conditions corresponding to the real operating conditions of the diesel engine D243 that equips AZPI nozzles. For the investigated injection regime (corresponding to the rated operating conditions of the D243 diesel engine, see Figure 18), the main portion of the fuel (74% of cycle delivery) is injected into the cylinder when the nozzle needle is at the maximum lift.…”
Section: Flow Passage Geometry Of Nozzlesmentioning
confidence: 99%
“…The emulsifier keeps biofuel and water from separating, stabilizing the combination. Emulsified biofuel can be used in diesel engines without considerable modifications [242] and may even outperform diesel [243]. Renewable sources may emit fewer particulates and nitrogen oxides.…”
Section: Emulsified Biofuelsmentioning
confidence: 99%
“…In the same context, Markov et al [96] investigated the physicochemical properties of rapeseed oil blends with diesel and emulsified multicomponent biofuel, studying its emissions, thermal efficiency, and nozzle inner flow, and then determined if the blends can be used as a replacement for diesel in internal combustion engines. The engine used to collect the data measurements was a diesel engine D-245.…”
mentioning
confidence: 99%